Efektifitas Antibakteri Infusa Daun Cengkeh (Syzygium aromaticum L.) terhadap Escherchia Coli - Wahyu Tusi Wardani; Rahmadhanti Dwi Andraini (STIKes Surya Global Yogyakarta, 2019)
Background: Cloves have an active bacteria-killing substance such as eugenol compound, eugenol acetate and caryophyllene. This research uses clove leaves because they have not been utilized maximally and still considered to be less useful waste. The main component in clove leaf essential oil is eugenol, in clove leaf essential oil is generally between 80-88%.Objective: The purpose of this research is whether clove leaf infusion has antibacterial activity toward Escherchia Coli and how much infusion concentration of clove leaf that is effective toward coli bacteria.Methods: This research was an experimental study by using purposive sampling method, with dry leaf criteria, brown color, and not moldy. Making extracts in this study used the infundation method. This study used three concentrations of clove leaf infusion, namely with a concentration of 1.1%, 2.3%, 4.5%. The antibacterial test used the Kirby Baure method to determine the sensitivity of gram-negative microorganisms Escherchia coli.Results: The results in this study were iradical that from various concentrations in clove leaf infusion samples 1.1%, 2.3%, 4.5% could cause antibacterial effectiveness toward Escherchia coli. The concentration of clove leaf infusion that is effective toward Escherchia coli bacteria is a concentration of 4.5%. Test statistical analysis used One Way One Anova Analysis. Based on the results, there were significant differences between all groups because of the sig. 0.05. While the One Way Anova Post Hoc Analysis test results have 2 results, there was no difference and there were significant differences between treatments.Conclusion: Clove leaf infusion can cause antibacterial effectiveness toward Escherchia coli.Keywords: Clove leaf infusion, Kirby Baure Method, Escherchia coli.